Lenalidomide Enhances CAR-T Cell Activity Against Solid Tumor Cells. (22nd September 2020) - Wang, Zhixiong; Zhou, Guomin; Risu, Na; Fu, Jiayu; Zou, Yan; Tang, Jiaxing; Li, Long; Liu, Hui; Liu, Qian; Zhu, Xuekai
Chimeric antigen receptor (CAR) T-cell immunotherapy still faces many challenges in the treatment of solid tumors, one of which is T-cell dysfunction or exhaustion. Immunomodulator lenalidomide may improve CAR T-cell function. In this study, the effects of lenalidomide on CAR T-cell functions (cytotoxicity, cytokine secretion, and cell proliferation) were investigated. Two different CAR T cells (CD133-specific CAR and HER2-specific CAR) were prepared, and the corresponding target cells including human glioma cell line U251 CD133-OE that overexpress CD133 and human breast cancer cell line MDA-MB-453 were used for functional assay. We found that lenalidomide promoted the killing of U251 CD133-OE by CD133-CAR T cells, the cytokine secretion, and the proliferation of CD133-CAR T cells. Lenalidomide also enhanced the cytotoxicity against MDA-MB-453 and the cytokine secretion of HER2-CAR T cells but did not affect their proliferation significantly. Furthermore, lenalidomide may regulate the function of CAR T cells by inducing the degradation of transcription factors Ikaros and Aiolos.